Perlindungan hukum pemegang kartu kredit yang dirugikan dengan penawaran asuransi menggunakan media elektronik - Rahmawati Rahmawati (Jurnal Cakrawala Hukum, 2022)
This research concerns the protection of credit card customers who are harmed by the provider through telemarketing or short messages and other forms of responsibility for credit cardholders. The study of normative law is carried out with a statutory, conceptual, and case approach, as well as the purpose of grammatical, systematic, and theological interpretation. The results of this study indicate that with the Circular of the Financial Services Authority No. 12/SE.07/OJK/2014 regarding the delivery of information related to the marketing of fund products or financial services, preventive measures can be taken. Every financial service actor to stop any business offering their products and services by telephone or short message, Bank Indonesia Regulation Number: 7/6 / PBI / 2005 concerning Calculation of Information Disclosure of Banking Products and Use of Customer Personal Data, as well as the Civil Code. In the form of repressive legal protection against criminal, civil and administrative sanctions. The criminal threat that can be imposed is a maximum imprisonment of (four) years. As well as civil sanctions in the form of compensation for a number of losses suffered by the Customer (cardholder).